Prezi as an innovative teaching tool for the strengthening of significant learning - Sanchez, Paola Katherine Moreira; Pazmino, Marcos Fernando; Gamez, Maria Rodriguez (International research journal of management, IT and social sciences, 2020)
The purpose of this research is to determine the implementation of innovative teaching tools, for the strengthening of significant learning, applied by teachers, in the teaching-learning process. By using innovative resources, it allows students to orient and build knowledge in all disciplines, the use of Prezi pursues, that learning is meaningful, the purpose of study is focused on analyzing the use of innovative teaching tools in the teaching process, through observation and survey techniques, in order to improve learning, it was also possible to detect that the origin of the problem is the low use of the application of innovative digital tools that serve as support in the planning of the different subjects in a creative and interactive way in the process.